Pengaruh Penerapan Whistleblowing System terhadap Tindak Kecurangan dengan Independensi sebagai Moderator - Pramudyastuti, Octavia Lhaksmi; Rani, Utpala; Nugraheni, Agustina Prativi; Susilo, Ghina Fitri Ariesta (Universitas Pendidikan Ganesha, 2021)
Acts of fraud and corruption are still the main problems in Indonesia. This country needs a new method, namely a whistleblowing system or a violation reporting system as an early detection that minimizes fraud. This study aims to investigate the moderating effect of auditor independence on the relationship of whistleblowing systems and fraud. Data was collected employing surveys and interviews with auditors and Supervisors for the Implementation of Government Affairs in the Regions (P2UPD) at the Provincial Inspectorate X. Data analysis was carried out using moderated regression analysis (MRA) and the test results indicated that there was anecdotal evidence that auditor independence weakens the effect whistleblowing system implementation on the intensity of fraud that can be found by the auditor. This indicates that auditors who have high independence tend to ignore the existence of theÂ whistleblowing systemÂ to find fraudulent acts.